Visualizing and analyzing 3D biomolecular structures using Mol* at RCSB.org: Influenza A H5N1 virus proteome case study - Bittrich, Sebastian; Rose, Alexander S; Sehnal, David; Duarte, Jose M; Rose, Yana; Segura, Joan; Piehl, Dennis W; Vallat, Brinda; Shao, Chenghua; Bhikadiya, Charmi; Liang, Jesse; Ma, Mark; et al. (Protein science, 2025)
The easiest and often most useful way to work with experimentally determined or computationally predicted structures of biomolecules is by viewing their three-dimensional (3D) shapes using a molecular visualization tool. Mol* was collaboratively developed by RCSB Protein Data Bank (RCSB PDB, RCSB.org) and Protein Data Bank in Europe (PDBe, PDBe.org) as an open-source, web-based, 3D visualization software suite for examination and analyses of biostructures. It is capable of displaying atomic coordinates and related experimental data of biomolecular structures together with a variety of annotations, facilitating basic and applied research, training, education, and information dissemination. Across RCSB.org, the RCSB PDB research-focused web portal, Mol* has been implemented to support single-mouse-click atomic-level visualization of biomolecules (e.g., proteins, nucleic acids, carbohydrates) with bound cofactors, small-molecule ligands, ions, water molecules, or other macromolecules. RCSB.org Mol* can seamlessly display 3D structures from various sources, allowing structure interrogation, superimposition, and comparison. Using influenza A H5N1 virus as a topical case study of an important pathogen, we exemplify how Mol* has been embedded within various RCSB.org tools-allowing users to view polymer sequence and structure-based annotations integrated from trusted bioinformatics data resources, assess patterns and trends in groups of structures, and view structures of any size and compositional complexity. In addition to being linked to every experimentally determined biostructure and Computed Structure Model made available at RCSB.org, Standalone Mol* is freely available for visualizing any atomic-level or multi-scale biostructure at rcsb.org/3d-view.
Keywords: internet; pandemic preparedness; Models, Molecular; Influenza A Virus, H5N1 Subtype; 3D biostructure; viral pathogen; web‐based; global health; Internet; virus chřipky A, podtyp H5N1; open‐source; virus life cycle; molecular visualization; Protein Conformation; Proteome; molekulární modely; Viral Proteins; databáze proteinů; Software; influenza A H5N1 virus; Databases, Protein; Protein Data Bank; proteom; software; virové proteiny; konformace proteinů